Edukasi Petani Terhadap Pencemaran Udara Pada Skala Rumah Tangga (Househol Air Pollution) Di Desa Tridana Mulya - Sumarlin Sumarlin (LP3M Universitas Muhammadiyah Kendari, 2021)
Knowledge of farming communities in Desa Tridana Mulya before and after household air pollution (HAP) is described in this study. Using quantitative methods, generally farmers' knowledge about air pollution in a household is still low (low category 60%; medium 3%; high 5%). One alternative to increase the knowledge of these farmers is through counselling activities on air pollution in the household. After the knowledge extension activities, the farmers were categorized as high as 70%, medium 25% and low 5%). Shows Spearman's correlation test that P-value = 0.005 is smaller than the α value = 0.01, so H0: ρs = 0 is rejected, this meaning knowledge of the farming community before and after being given counselling a significant correlation. Counselling can significantly. increase farmers' knowledge about air pollution household (HAP).